Behaviour and Welfare of Dairy Buffaloes: Pasture or Confinement? - Mora-Medina, Patricia; Berdugo-Gutiérrez, Jesús Alfredo; Mota-Rojas, Daniel; Ruiz-Buitrago, Jhon Didier; Nava-Adame, José; Guerrero-Legarreta, Isabel (Journal of Buffalo Science, 2018)
This review seeks to integrate recent scientific findings on the behaviour of buffalo cows in different production systems. These issues are discussed in relation to the level of welfare that buffalo cows experience under different production systems. In extensive conditions, the level of welfare is high because the animals are free to express natural behaviours related to feeding (grazing, ruminating) and rest. In contrast, intensified livestock-raising methods and techniques (machine-milking, artificial breeding etc.), first developed for dairy cattle are increasingly being used with water buffaloes in order to increase milk production. Greater knowledge of the biology of dairy buffaloes in aspects linked to physiology, behaviour, and health, together with needed adjustments to their production systems, will indicate options for improving the levels of comfort and welfare of these animals and contribute to increasing the efficiency of this type of dairy production. It is necessary to appreciate the importance of welfare within the entire chain of animal production since each of the scientific aspects considered in this manuscript reflects that animal welfare is not an absolute term, but multidisciplinary, with direct consequences on productivity. The welfare of animals in the production systems must be considered with the aim of ensuring an adequate nutritional, clinical, sanitary and behavioural status of the animals. When these aspects are achieved, production can be maximized and, for this reason, it is essential to maintain a balance between welfare and productivity.